Infant growth is associated with parental education but not with parental adiposity – Early Stockholm Obesity Prevention Project. (17th January 2014) - Svensson, V; Ek, A; Forssén, M; Ekbom, K; Cao, Y; Ebrahim, M; Johansson, E; Nero, H; Hagströmer, M; Ekstedt, M; Nowicka, P; Marcus, C
Abstract Aim To explore the simultaneous impact of parental adiposity and education level on infant growth from birth to 12 months, adjusting for known early‐life risk factors for subsequent childhood obesity. Methods Baseline data for 197 one‐year‐old children and their parents, participating in a longitudinal obesity intervention, were used. Obesity risk groups, high/low, were defined based on parental body mass index (n = 144/53) and parental education (n = 57/139). Observational data on infant growth between 0 and 12 months were collected. The children's relative weight (body mass index standard deviation score) at 3, 6 and 12 months and rapid weight gain 0–6 months were analysed in regression models, with obesity risk as primary exposure variables, adjusting for gestational weight gain, birth weight, short exclusive breastfeeding and maternal smoking. Results Relative weight at 3, 6 and 12 months was associated with low parental education but not with parental adiposity. No significant associations were observed with rapid weight gain. None of the early‐life factors could explain the association with parental education. Conclusion Low parental education level is independently associated with infant growth, whereas parental obesity does not contribute to a higher weight or to rapid weight gain during the first year.